2013
DOI: 10.22401/jnus.16.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Mercaptobenzimidazole and Some of its Derivatives

Abstract: The present work involved three steps: First step include synthesis of 2-mercaptobenzimidazole from reaction of o-phenylenediamine with carbon disulfide, in the second step: Alkylation of the 2-mercaptobenzimidazole with different alkyl halides or aryl to obtain thioether compounds. Third step: include oxidation of 2-mercaptobenzimidazole to disulfide, while oxidation of thioether compounds gave sulfone compounds by using hydrogen peroxide as oxidizing agent for (1-2h) with stirring at room temperature. The 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
(18 reference statements)
0
10
0
2
Order By: Relevance
“…The antimicrobial screening of some of the synthesized compounds was carried out using Kirby–Bauer disc diffusion method . Briefly, 100 μL of the tested bacteria/fungi were grown in 10 μL of fresh media until they reached a count of approximately 108 cells per mL for bacteria or 105 cells per mL for fungi . 100 μL of microbial suspension was spread onto agar plates corresponding to the broth in which they were maintained.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial screening of some of the synthesized compounds was carried out using Kirby–Bauer disc diffusion method . Briefly, 100 μL of the tested bacteria/fungi were grown in 10 μL of fresh media until they reached a count of approximately 108 cells per mL for bacteria or 105 cells per mL for fungi . 100 μL of microbial suspension was spread onto agar plates corresponding to the broth in which they were maintained.…”
Section: Resultsmentioning
confidence: 99%
“…2-(Methylthio)-1H-benzimidazole 1b was synthesized by a two-step procedure according to an earlier reported method. [35] In a 250-ml round-bottom flask, o-phenylenediamine (2.0 g) was dissolved in absolute ethanol (50 ml) and then carbon disulfide (14 ml) was added. The N-substituted 2-bromoacetamides 3a-i were synthesized by an earlier reported method.…”
Section: Synthesis Of 2-(methylthio)-1h-benzimidazole (1b)mentioning
confidence: 99%
“…The spectra of the ligand exhibited band at 1514 cm -1 due to the V(C=N) group of the ligand and when the complexes were formed this spectra were shifted to higher or lower frequency in the range (1622-1490)cm -1 which indicate that the ligand was bonded to the metal ion through N atom of V(C=N)group (Kennedy et al, 1972, Mohammed et al, 2013, Anandarajagopal et al, 2010, Ganesh et al, 2011, Akira et al, 1970, Rehman et al, 2013, also the ligand showed band at (736)cm -1 due to the V(C-S) group of the ligand and this band was shifted to higher or lower frequency in the range (742-725)cm -1 during the complexes which indicate that the ligand was bonded to the metal ion through sulphur atom (Zora et al, 2002, Butrus et al, 2012, Irshad et al,2010, Khullar et al,1975 .The infrared spectra of the prepared complexes show band in the range (451-412) cm -1 , which are attributed to V (M-N) . On the other hand, it has been observed that in the spectra of all compounds, the bands at (310-290) cm -1 were assigned to V (Hg-S) (Carlo et al, 1977, Musa, 1998, Awaz, 2015.…”
Section: Infrared Spectra For the Ligand And Prepared Complexesmentioning
confidence: 99%